Enhancing chickpea yield through the application of sulfur and sulfur-oxidizing bacteria - Jafar Nabati; Afsaneh Yousefi; Alireza Hasanfard; Zahra Nemati; Nastaran Kahrom; Ali Malakshahi Kurdestani (Scientific Reports)
Abstract Plant growth-promoting microorganisms can enhance sulfur uptake and boost crop production. This study was conducted to evaluate the changes in physiology, metabolism, and yield of chickpeas following the application of sulfur and two microbial consortia: (1) Thiobacillus sp., Bacillus subtilis, Paraburkholderia fungorum, and Paenibacillus sp.; and (2) Enterobacter sp. and Pseudomonas sp. The soil amendment involving a combination of sulfur and sulfur-oxidizing bacteria (SOB) in any quantity had positive effects on the availability of phosphorus, nitrogen, and potassium in the soil. A combination of 90% sulfur with Enterobacter sp. and Pseudomonas sp. resulted in a decrease in soil pH after harvesting in both years. Both years showed a strong correlation between soil pH and soil macronutrient concentration. In both years, the maximum grain yield was achieved through a combination of increased sulfur levels and SOB. The results reveal that sulfur application and SOB can increase nutrient availability, nutrient uptake, and yield of chickpea growth in calcareous soils.